The Role Of Discussion Method In Enhancing Speaking Skills Among Undergraduate Arabic Students At The New College Chennai - Zubair K M A, Ahamed; Ali, M.Yasar Arafath; Lebbai, Nahvi Muhiyadeen; Basith, M Abdul; Yousuf, R. Md. (Ijaz Arabi Journal of Arabic Learning, 2025)
The impact of the discussion method on the speaking skills of undergraduate Arabic students at The New College, Chennai, India, warrants a thorough examination. This study aims to determine how significantly the discussion method affects students' speaking abilities. It employs a quantitative research approach using a saturated sampling technique, with research instruments including questionnaires, interviews, and documentation, encompassing 26 Arabic undergraduate students from the 2022-25 cohort. The findings indicate that implementing the discussion method in teaching Speaking Skills effectively engaged students' interest in learning and was relatively easy to follow. According to the results of the T-test, the calculated value (t_hitung) is 9.648, which exceeds the table value (t_table) of 2.056 at a significance level of 0.025. Hence, the alternative hypothesis (Ha) is accepted. In contrast, the null hypothesis (Ho) is rejected, concluding that the discussion method positively influences the Speaking Skills of undergraduate students at The New College, Chennai. Additionally, the coefficient of determination test yielded a result of 0.782, indicating that the discussion method accounts for 78.2% of the variance in Speaking Skills.